Pengaruh Manajemen Risiko dan Karakteritsik Komite Audit Terhadap Kinerja Keuangan Perusahaan - Salwa Azaria (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study has the objective of knowing the effect of risk management and the characteristics of the audit committee in the financial performance of a company in various industrial sectors listed on the Indonesia Stock Exchange (IDX) in 2019-2021. This study was conducted by analyzing secondary data through the company's annual report and using purposive sampling as a sampling technique. In this analysis the technique used in the analysis is multiple linear analysis. And the results of this study also show that risk management, audit committee independence, meeting frequency, and audit committee size have no influence on financial performance. However, the competence of an audit committee also influences the company's financial performance.